2021
DOI: 10.5483/bmbrep.2021.54.2.210
|View full text |Cite
|
Sign up to set email alerts
|

The role of the voltage-gated potassium channel, Kv2.1 in prostate cancer cell migration

Abstract: Voltage-gated potassium (Kv) channels are involved in many important cellular functions and play pivotal roles in cancer progression. The expression level of Kv2.1 was observed to be higher in the highly metastatic prostate cancer cells (PC-3), specifically in their membrane, than in immortalized prostate cells (WPMY-1 cells) and comparatively less metastatic prostate cancer cells (LNCaP and DU145 cells). However, Kv2.1 expression was significantly decreased when the cells were treated with anti-oxidants, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Blockade of Kv2.1 results in cell migration inhibition, without affecting cell proliferation. Further experiments suggest that ROS reduction with Nacetyl-l-cysteine or ascorbic acid results in Kv2.1 downregulation [25]. These data suggest that Kv2.1 might be a part of ROS-related signaling and link ROS formation with tumor metastatic potential in prostate cancer.…”
Section: Potassium Channelsmentioning
confidence: 81%
See 2 more Smart Citations
“…Blockade of Kv2.1 results in cell migration inhibition, without affecting cell proliferation. Further experiments suggest that ROS reduction with Nacetyl-l-cysteine or ascorbic acid results in Kv2.1 downregulation [25]. These data suggest that Kv2.1 might be a part of ROS-related signaling and link ROS formation with tumor metastatic potential in prostate cancer.…”
Section: Potassium Channelsmentioning
confidence: 81%
“…Moreover, studies have shown that VGPC-induced electrical excitability in cancer cells affects metastatic invasiveness. It has been suggested that Kv2.1 might play a role in the migration of prostate cancer cells [25]. Increased expression enhances bone marrow mesenchymal stem cell migration under hypoxic preconditioning [26].…”
Section: Potassium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the Kv2.1 channel recently was reported to be higher in the metastatic prostate cancer cells (PC3), and their blockade with stromatoxin-1 or siRNA significantly inhibits the migration of malignant prostate cancer cells. 51 This channel as Kv1.4, Kv4.2, Kv7.1 and large-conductance Ca 2+ -activated K + channel (BK Ca ) also showed a high expression in the CD133 + subpopulation of SH-SY5Y neuroblastoma cells. 52 Increased levels of Kv3.4 channel expression were identified in OSCC (oral squamous cell carcinoma).…”
mentioning
confidence: 99%
“…For example, voltage-gated sodium channels (VGSCs) can enhance extracellular matrix (ECM) degradation and facilitate the metastasis of various carcinomas (15)(16)(17)(18). Meanwhile, the role of K v channels in tumour proliferation and growth has been demonstrated as applicable to a variety of cancer, including prostate cancer, colon cancer, lung cancer, and breast cancer (19)(20)(21)(22)(23). Therefore, regulating the activity of ion channels is one of the viable solutions for the anticancer treatment.…”
mentioning
confidence: 99%